De kan hverken ryge eller rejse: Rygeforbuddet i danske fængsler - Linda Kjær Minke; Ayo Næsborg-Andersen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract In 2017, a smoking ban was introduced in Danish prisons and detention centers. In some of these institutions, inmates are locked in for up to 23 hours per day. The only time inmates can smoke are when staff accompanies them outside to smoke. The smoking ban was instituted to avoid exposing staff and fellow inmates to passive smoking. If a prisoner violates the smoking ban, a disciplinary punishment is imposed. The punishment is up to five days in a penalty cell (solitary confinement). This article discusses whether the smoking ban interferes with the basic human rights of prisoners as expressed by the European Convention on Human Rights (ECHR). The smoking ban in Danish prisons is then compared to the rules governing residential homes in order to examine whether it violates the principle of equal treatment. Finally, the article discusses whether the penalty for violating the smoking ban is proportional to the purpose of the ban on smoking. The article concludes that a prisoner’s right to smoke in his or her cell is probably not covered by Article 3 of the ECHR, but rather by Article 8. This is because the smoking ban appears to be neither proportional nor necessary since the previous set of rules – where prisoners were allowed to smoke in their cells, but not allowed to smoke in the common areas of the prison – served the same purpose, but far less intrusively. In addition, the smoking ban likely constitutes discrimination against inmates, cf. ECHR Article 14 in conjunction with Article 8, as residents of residential homes can smoke in their accommodations.